Book review: Kravchenko S. A. “Sociology of Digitalisation: university textbook” - N. N. Meshcheryakova; L. A. Vasilenko (Цифровая социология)
The review of a new book written by a leading Russian sociologist-theorist Sergey A. Kravchenko is presented. The book analyses the social implications and prospects of the digitalisation. The objectivity of this process leading to the complication of society, its dehumanisation and the emergence of new previously unseen risks, is noted. Scientific and technological innovations reduce the share of traditional risks, natural and technological, but increase the share of institutional risks. Sergey A. Kravchenko calls this new reality the socio-digital-natural reality, in which, primarily in social networks, both human actors and non-human (digital) actors, sociotechnical and techno-social hybrids operate. The author of the book being reviewed concludes that there is a need for a humanistic digital turn, a change in approaches and focus of modern scientific knowledge, which should be integrated and multidisciplinary, based on the social and natural sciences integration, aimed at the analysis of disequilibrium systems in which disequilibrium, turbulence do not exclude the tendencies towards organisation and self-organisation.The peer-reviewed work is an educational publication and it is aimed at developing students’ ability to think critically about the consequences of digitalisation and make balanced managerial decisions. It introduces students to the most modern and advanced sociological theories and concepts.